2009
DOI: 10.1007/s00464-009-0516-1
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal dilation after laparoscopic adjustable gastric banding: a more systematic approach is needed

Abstract: Laparoscopic adjustable gastric banding causes esophageal dilation in about half of patients. This dilation is correlated with symptoms and is partly reversible after emptying of the band. The clinical relevance of the dilation is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Esophageal motility showed an increased number of defective propagations, LES relaxation was disturbed and resting pressure decreased. These synergistic factors promote esophageal and pouch dilation,7 19 and larger overall esophageal diameter,20 potentially leading to an epiphrenic diverticulum as a late complication with its own aspiration risk 21 22. Such a reservoir was not found in our patient, while achalasia and protracted pouch emptying were.…”
Section: Discussionmentioning
confidence: 66%
“…Esophageal motility showed an increased number of defective propagations, LES relaxation was disturbed and resting pressure decreased. These synergistic factors promote esophageal and pouch dilation,7 19 and larger overall esophageal diameter,20 potentially leading to an epiphrenic diverticulum as a late complication with its own aspiration risk 21 22. Such a reservoir was not found in our patient, while achalasia and protracted pouch emptying were.…”
Section: Discussionmentioning
confidence: 66%
“…However, the man-made obstruction near the esophageal-gastric junction may lead to esophageal dilation and motility dysfunction [19-21]. The long-term impacts of gastric banding are not well known because of a relatively short history of this procedure.…”
Section: Discussionmentioning
confidence: 99%
“…18 However, recent data showed that gastric banding leads to marked esophageal dilation and motility dysfunction with weakened contractions in the esophageal body. [19][20][21] The mechanism for the motility dysfunction in gastric banding patients is not clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, safety and efficiency of LAGB in long term (R5 years) is inconsistent. 6,11,12 The main complications of LAGB include band erosion, slippage, port infection, pouch and esophageal dilatation, and weight loss failure that usually end up in band removal. 13,14 In Iran, LAGB is also a common bariatric surgery that can result in various and some different outcomes.…”
mentioning
confidence: 99%